Improving Insulating and Wettability Properties of Titanium Alloys via Electrochemical Anodization - Yeji Choi; Chanyoung Jeong (Corrosion science and technology, 2025)
In this study, anodization was applied to Titanium (Grade 4) alloy to form nanostructured oxide films and resulting changes in surface properties were systematically investigated with respect to anodization time. As the duration of anodization increased, the oxidation reaction was intensified, leading to a progressive thickening of the TiO2 layer. Energy Dispersive X-ray Spectroscopy (EDS) analysis confirmed a gradual increase in oxygen content with a corresponding decrease in titanium content. Additionally, enlargement of pores and surface roughness with longer anodization times resulted in reduced contact angles, indicating enhanced hydrophilicity. Electrical resistance measures revealed that thicker oxide layers effectively impeded electron flow, thereby exhibiting superior insulating characteristics than thinner oxide layers. Overall, these results demonstrate that anodization is a promising surface modification technique for a wide range of applications, including energy devices and electronic components. In particular, the TiO2 oxide layer holds significant potential as a high-performance surface material due to its excellent insulating properties and improved wettability.